Evaluación del efecto de tres fertilizantes orgánicos líquidos mediante sistema de riego por goteo para la producción del cultivo de frutilla orgánica (Fragaria ananassa var. albión) en el sector del barrio 10 de agosto de la ciudad de Ibarra en la provincia de Imbabura - Andrade Pinto, Jorge Luis (2021)
The fruit producers of the province of Imbabura present the problem of the increase in the use of chemical fertilization in recent years, due to this problem the consequences are the lack of knowledge of the farmers when carrying out a fertilization without any technical guide, the contamination of the soil and water sources, environmental pollution, increased production costs in their crops and among others. For this reason, the main objective of this research was to compare the effect of three liquid organic fertilizers on the production of organic strawberry crops (Fragaria ananassa var. albión) in the 10 de august neighborhood of the city of Ibarra. A completely randomized block design (DBCA) with four treatments and three replications was applied, giving a total of twelve experimental units. The treatments were: T1: Liquid organic fertilizer type 1 (semi complete), T2: Liquid organic fertilizer type 2 (complete), T3: Liquid organic fertilizer type 3 (simple) and T4: Control (chemical fertilizer). The variables under study were: plant height at 30, 60 and 90 days (cm), percentage of plant mortality (% of dead plants), days to flowering (days), number of fruits per plant (No. fruits/plant), total fruit yield extracted per experimental unit (kg), Brix degrees of the fruit (ºBrix) and pH of the fruit. The results showed that the best treatment for each variable was: plant height at 30, 60 and 90 days was the T2 that reached an average at 90 days of (21.53 cm), percentage of mortality of the plants of ( 0.74%), days to flowering was the earliest T2 with (55 days), the number of fruits per plant was T2 that reached an average at 120 days with (6.70 fruits/plants), yield total fruit extracted per experimental unit was T2, which reached an average at 120 days with (6.10 kg), Brix degrees of the fruit was T2 with (12.23ºBrix) and the pH of the fruit was T2 with (3 ,40). Therefore, the T2 where the liquid organic fertilizer type 2 (complete) was applied had higher development and yield in the study area.